Eating Disorder Risk and Severity as a Function of Following Self-Administered Popular Diets. (29th May 2020) - Shahan, Mackinsey; Jordan, Katherine; Siegfried, Nicole; Douglas, Crystal; Lawrence, Jeannine
Abstract: Objectives: Adherence to popular diets has increased in recent years. This is concerning as extreme dieting behaviors, which may develop as a result of following certain diets, can increase risk for developing an eating disorder (ED). We assessed whether adherence to popular diets (i.e., gluten free, vegetarian, paleo, and clean eating) is related to ED diagnosis and severity. We hypothesized that adherence to any popular diet would be associated with ED risk, while adherence to an increasing number of diets would be associated with ED severity. Methods: Adult women admitted to an intensive outpatient or partial hospitalization program for ED treatment were recruited to participate. Demographic information (age and race), ED diagnosis and severity (identified by a trained clinician and scored by the Eating Disorder Inventory 3 (EDI-3)), and height and weight were collected. A self-administered survey assessed diet history. Results: Seventy-seven women aged 26.74 years (SD = 7.71), primarily white (89.6%), with an ED diagnosis (48.1% anorexia nervosa (AN); 20.8% bulimia nervosa (BN), 16.9% binge eating disorder (BED), and 14.3% "eating disorder not otherwise specified" (EDNOS)) participated. The majority (63.6%) reported currently or previously following a minimum of one pre-selected diet and 7.8% indicated following all four diets at some time point. Diet history was related to ED diagnosis (x2 = 15.981, P = 0.014), particularly among participants diagnosed with AN, BN, or EDNOS. Adherence to specific diets, including gluten free or vegetarian, was not associated with ED diagnosis (x 2 = 11.422, P = 0.076 and x 2 = 7.789, P = 0.254, respectively), although adherence to paleo and clean eating were more commonly followed by participants diagnosed with EDNOS (x 2 = 9.419, P = 0.151 and x 2 = 12.307, P = 0.055, respectively). Paleo diets were significantly associated with 3 of the 6 EDI-3 composite scores ( P < 0.05), whereas vegetarian was associated with 1, and clean eating and gluten free were not associated with ED severity. Conclusions: More restrictive diets, or those that require increased effort to learn and follow (i.e., paleo and clean eating), were more strongly associated with an EDNOS diagnosis. Assessment of dieting history may be clinically useful to better identify and diagnose patients with EDs in the future. Funding Sources: No funding to report.